Simulation in Surgery: What's Needed Next?. Issue 5 (May 2015) - Stefanidis, Dimitrios; Sevdalis, Nick; Paige, John; Zevin, Boris; Aggarwal, Rajesh; Grantcharov, Teodor; Jones, Daniel B.
Abstract : Objective: To review the current state of simulation use in surgery and to offer direction for future research and implementation of evidence-based findings. Background: Simulation-based training (SBT) in surgery has surged in recent years. Although several new simulators and curricula have become available, their optimization and implementation into surgical training has been lagging. Methods: Members of the Association for Surgical Education Simulation Committee with expertise in surgical simulation review and interpret the literature and describe the current status of the use of simulation in surgery, identify the challenges to its widespread adoption, and offer potential solutions to these challenges. The review focuses on simulation research and implementation of existing knowledge and explores possible future directions for the field. Results: Skill acquired on simulators has repeatedly and consistently been demonstrated to transfer to the operating room, and proficiency-based training maximizes this benefit. Several simulation-based curricula have been developed by national organizations to support resident training, but their implementation is lagging because of inadequate human resources, difficult integration of SBT into educational strategy, and logistical barriers. In research, lack of coordinated effort, flaws in study design, changes in simulator-validation concepts, limited attention to skill retention, and other areas are in need of improvement. Conclusions: Future research in surgical simulation should focus on demonstrating the cost-effectiveness of SBT and its impact on patient outcomes. Furthermore, to enable the more widespread incorporation of best practices and existing simulation curricula in surgery, effective implementation strategies need to be developed. Abstract : The Association for Surgical Education Simulation Committee evaluates the current use of simulation in surgical training, identifies challenges, and offers potential solutions to these challenges in both research and implementation of existing best practices and curricula.